Taxonomic revision and molecular phylogeny of Gymnocorymbus Eigenmann, 1908 (Teleostei, Characiformes, Characidae) - Benine, Ricardo C. [UNESP]; Melo, Bruno F. [UNESP]; Castro, Ricardo M. C.; Oliveira, Claudio [UNESP] (Magnolia Press, 2015)
Characidae, one of the most diverse families of Characiformes and one of the largest clades of fishes in the world, has a complex taxonomic background, with one issue being the placement of various genera, including Gymnocorymbus. Herein, we generate the first molecular phylogeny for the genus using three nuclear and two mitochondrial loci and review the systematics of Gymnocorymbus. This genus includes the black tetra, a well-known and popular species among aquarists. Molecular phylogeny strongly supports the monophyly of Gymnocorymbus, with this hypothesis corroborated by the presence of three morphological synapomorphies. Of the six previously known nominal species of Gymnocorymbus, three are considered valid herein: Gymnocorymbus bondi from the Rio Orinoco basin, Gymnocorymbus ternetzi from the Rio Paraguay basin, and Gymnocorymbus thayeri from the Corantijn and Amazon basin and rivers of northeastern Brazil. A fourth species, Gymnocorymbus flaviolimai sp. n., is described from the Rio Madeira, Amazon basin. Lectotypes are designated for G. ternetzi and G. thayeri. Our results support previous hypotheses of the alignment of Gymnocorymbus close to the subfamily Stethaprioninae and also support the sister relationship between G. ternetzi and G. thayeri, and of that clade as sister to G. bondi.
Keywords: Freshwater fishes; Multilocus analysis; Stethaprioninae; Stichonodon; Systematics